Thyroid Functions in Children on Levetiracetam or Valproic Acid Therapy - Karatoprak, Elif; Paksoy, Samet (Journal of Pediatric Epilepsy, 2020)
The aim of this study was to investigate the thyroid functions in children receiving levetiracetam or valproate monotherapy. We retrospectively reviewed the records of children with controlled epilepsy receiving valproic acid (VPA group) or levetiracetam monotherapy (LEV group) for at least 6 months. Free thyroxine 4 levels (fT4) and thyroid stimulating hormone (TSH) levels were compared between VPA group, LEV group, and age- and gender-matched healthy children (control group). A total of 190 children were included in the study: 63 were in the VPA, 60 in the LEV, and 67 in the control group. Although there was no significant difference regarding average fT4 levels, higher TSH levels were found in the VPA group when compared with the LEV and control groups (p < 0.001 and p < 0.001, respectively). There was no significant difference in terms of fT4 and TSH values in the LEV group when compared with the control group (p = 0.56 and p = 0.61, respectively). Subclinical hypothyroidism (defined as a TSH level above 5 uIU/mL with a normal fT4 level was detected in 16% of patients in the VPA group, none in the LEV and control groups. Our study found that VPA therapy is associated with an increased risk of subclinical hypothyroidism while LEV had no effect on thyroid function tests.
Keywords: antiepileptic drugs; thyroid function; children